What do environmental advertisers Say and how does the public understand them? Contributions to education for sustainability - Campos, Natália Aparecida (2021)
Different strategies focused on mitigating, remedying, or preventing the intensification of environmental issues have been adopted by several institutions, organizations, governments, media, among others. One of these strategies lies on environmental advertising campaigns based on creative and eye-catching advertisements aimed to promoting the environmental cause. However, the literature lacks studies focused on investigating how efficient these campaigns are in achieving their goals, as well as how individuals interpret/understand them. Thus, the aim of the current study is to carry out the systemic assessment of different environmental advertisements by taking into consideration their linguistic features and specific contents, the emotional reactions they induce in different individuals and the way the target audience interprets/understands them. In order to do so, 367 advertisements were evaluated, and 350 volunteers responded to an online questionnaire that enabled assessing individuals' reactions and how they interpreted them. Data have shown great diversity of advertisements; whose features elicit different reactions in the public. Advertisements focused on exploiting strong images aroused melancholic and fearful feelings in individuals. Subjective or more robust linguistic resources did not make it easier for the public to understand them and advertisements focused on exploring environmental issues in a more pleasant and creative way were able to rise greater public interest in them. To the best of our knowledge, the current study is pioneer in conducting a comprehensive assessment of environmental advertisements worldwide in order to indicate how they can help improving environmental education, as well as to encouraging greater population engagement to environmental causes.